The role of love of money on employees' organizational commitment: do ethics and pay satisfaction matter? / Su'un Su'un ... [et al.] - -, Su'un Su'un; Rahim, Syamsuri; Nurwanah, Andi; -, Junaidi Junaidi; Randy Ariyadita Putra, Randy Ariyadita Putra (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
This research investigated the role of Love of Money (LOM) in influencing employees' organisational commitment, which is mediated by ethics and pay satisfaction. The research applied a cross-sectional survey method to collect 680 participants among university employees in Sulawesi Selatan, Indonesia. Structural equation modelling (SEM) was used to examine the research hypotheses. The result showed that Love of Money plays an important role in employees' commitment to organisations. Additionally, this study confirmed that employees' ethics and pay satisfaction significantly mediated the relationship between Love of Money and organisational commitment. The t study provides insight into theoretical and managerial implications to help academicians and regulators improve organisations' operation systems through the triangular Theory of Love. The current study was limited to Indonesian government employees; there is a future need to study employees' attitudes and behaviours across cultures and regions.